2006
DOI: 10.1002/ccd.20549
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital administration of enoxaparin before primary angioplasty for ST‐elevation acute myocardial infarction

Abstract: We hypothesized that primary percutaneous coronary intervention (PCI) could be performed with prehospital injections of enoxaparin for ST segment elevation myocardial infarction (STEMI). Enoxaparin has been studied in combination with fibrinolysis in STEMI, but has not been evaluated as anticoagulant regimen for primary PCI. In a prospective registry, 143 consecutive patients with STEMI received prehospital 0.5 mg/kg intravenous (i.v.) bolus followed by 1 mg/kg subcutaneous enoxaparin before immediate transpor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 33 publications
0
10
0
1
Order By: Relevance
“…10 In the present study, sufficient time (144 min) was allowed for heparin to affect IRA patency. Moreover, the proportion of patients transferred from other hospitals was relatively small (29%), and thus avoids selection bias from the route of admission, as was supported by our subgroup analysis of non-referred patients.…”
Section: Effect Of Early Heparin On Initial Ira Patencymentioning
confidence: 91%
See 2 more Smart Citations
“…10 In the present study, sufficient time (144 min) was allowed for heparin to affect IRA patency. Moreover, the proportion of patients transferred from other hospitals was relatively small (29%), and thus avoids selection bias from the route of admission, as was supported by our subgroup analysis of non-referred patients.…”
Section: Effect Of Early Heparin On Initial Ira Patencymentioning
confidence: 91%
“…[7][8][9][10] Of these 3 patients, 2 who had been treated with abciximab experienced profuse bleeding in the oral cavity or at a tracheostomy site, and both required a massive blood transfusion after PCI, but finally succumbed to hypovolemic shock. The other patient, who had not been treated with abciximab, developed retroperitoneal hematoma and recovered from transient hypovolemic shock after a blood transfusion.…”
Section: Bleeding Complicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three studies of PCI after fibrinolysis resulted in favorable outcome when enoxaparin was compared with UFH (LOE 4 397,432 ; LOE 5 394 ). Eight other studies showed no benefit using enoxaparin compared with UFH (LOE 2 342,433,434 ; LOE 4 405,409,435,436 ; LOE 5 345 ).…”
Section: Consensus On Sciencementioning
confidence: 97%
“…De hecho, el estudio fue diseñado sin suplementos intravenosos de enoxaparina, pero se produjeron tres trombosis de catéter en el grupo inicial, y se cambió la pauta de tratamiento a suplementos intravenosos. Labèque et al 13 también han estudiado la administración prehospitalaria de ENX antes de la AP en el IAMCEST. Ese grupo administró un bolo intravenoso de 0,5 mg/kg, seguido de 1 mg/kg subcutáneo, a nivel prehospitalario antes de la AP.…”
Section: Discussionunclassified